PROBLEMS AND SOLUTIONS IN THE ORGANIZATION OF ACCOUNTING IN THE HEALTH CARE SYSTEM. - Abdullayeva, Hilola (Центр Научных Публикаций (buxdu.uz), 2024)
This article presents analytical information about the health care system of our country, economic problems in this system, the process of accounting application, existing problems and solutions in the system of accounting application.